Front Cover Image, Volume 77, Issue 7. Issue 7 (10th June 2021) - Chong, Pablo; Essoh, Josué Ngando; Arango Isaza, Rafael E; Keizer, Paul; Stergiopoulos, Ioannis; Seidl, Michael F; Guzman, Mauricio; Sandoval, Jorge; Verweij, Paul E; Scalliet, Gabriel; Sierotzski, Helge; de Lapeyre de Bellaire, Luc; et al.
Abstract : The front cover image is based on the Research Article A world‐wide analysis of reduced sensitivity to DMI fungicides in the banana pathogen Pseudocercospora fijiensis by Pablo Chong et al., https://doi.org/10.1002/ps.6372 . Abstract : The front cover image is based on the Research Article A world‐wide analysis of reduced sensitivity to DMI fungicides in the banana pathogen Pseudocercospora fijiensis by Pablo Chong et al., https://doi.org/10.1002/ps.6372 .